2001
DOI: 10.1007/s004410000311
|View full text |Cite
|
Sign up to set email alerts
|

Regional and cellular expression of the mannose receptor in the post-natal developing mouse brain

Abstract: The mannose receptor, a glycoprotein expressed in a soluble and membrane form by macrophages, plays an important role in homeostasis and immunity. Using biochemical and immunohistochemical analyses, we demonstrate that this receptor, both in its soluble and membrane forms, is expressed in vivo in the post-natal murine brain and that its expression is developmentally regulated. Its expression is at its highest in the first week of life and dramatically decreases thereafter, being maintained at a low level throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
5
38
0
Order By: Relevance
“…They participate in C. albicans adhesion to endothelial surface, probably BBB, along with other cell wall components. Thus, according to previous studies [5,8], mannose receptors were found on cerebral blood vessel endothelium. In addition, they are expressed on macrophages [8] actively phagocytizing fungi.…”
Section: Resultssupporting
confidence: 52%
“…They participate in C. albicans adhesion to endothelial surface, probably BBB, along with other cell wall components. Thus, according to previous studies [5,8], mannose receptors were found on cerebral blood vessel endothelium. In addition, they are expressed on macrophages [8] actively phagocytizing fungi.…”
Section: Resultssupporting
confidence: 52%
“…Proteins were separated in SDS-polyacrylamide slabs gels using the discontinuous gel and buffer system of Laemmli (1970) with 8% polyacrylamide in the separate gel. After electrophoresis, the proteins were transferred to nitrocellulose paper, which was incubated for 60 min with a rabbit anti-GLUT1 polyclonal antibody (1 : 200), a rabbit anti-MR polyclonal antibody (1 : 5000) (Burudi et al 1999;Burudi and Regnier-Vigouroux 2001) or a rabbit anti-Man II polyclonal antibody (1: 2000) (Moremen and Robbins 1991) in TBS containing 0.05% Tween-20. Thereafter, the paper was incubated for 60 min with an anti-rabbit IgG-AP conjugate.…”
Section: Glut1 Mannose Receptor (Mr) and Mannosidase II (Man Ii) Immmentioning
confidence: 99%
“…Although macrophages are known to express the CD206 receptor, there are conflicting reports on cell-specific expression within the adult CNS (11,20). To confirm the localization of CD206 expression to perivascular macrophages in our mouse model, we performed double labeling immunocytochemistry with anti-CD206 receptor and anti-glial fibrillary acidic protein (GFAP) or antiionized calcium-binding adaptor molecule-1 (Iba1) antisera to rule out astrocyte and microglia expression, respectively.…”
Section: Depletion Of Perivascular Macrophagesmentioning
confidence: 99%